Allgrove syndrome: Case series on 4A and triple a syndrome in children with rare presentation - Saheli Roy; Priyanka Gupta; Suprit Basu; Mrinal K Das; Sumana Datta (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Introduction: Allgrove or Triple A syndrome is a rare familial multisystem disorder with autosomal recessive inheritance. Usual features include varied combination of alacrima, achalasia cardia, and adrenocorticotrophic hormone (ACTH) resistant adrenal insufficiency along with autonomic dysfunction and other neurological problems in some cases when it is known as 4A syndrome. Basic defect is in the Achalasia Addisonianism Alacrima Syndrome gene (AAAS) located on chromosome 12q13. Case Details: This report relates to two unrelated girls aged 7 and 12 years, who presented with orbital cellulitis with acute adrenal crisis and initial episode of nephrotic syndrome, respectively. Both had history of hyperpigmentation of skin, especially palmer creases and knuckles and absence of tear from both eyes while first patient also had autonomic dysfunction. Ophthalmological examination, biochemical evaluations for adrenal function, barium swallow study and magnetic resonance imaging (MRI) of orbits were all consistent with Allgrove Syndrome. Patients were adequately treated for the complications and then put on hormone replacement therapy and ocular lubricants resulting in remarkable improvement on follow up study. Conclusion: Despite lack of definitive treatment, supportive treatment and hormone replacement can improve quality of life of Allgrove patients.